Cell-specific models reveal conformation-specific RAF inhibitor combinations that synergistically inhibit ERK signaling in pancreatic cancer cells - Sevrin, Thomas; Imoto, Hiroaki; Robertson, Sarah; Rauch, Nora; Dyn'ko, Uscinnia; Koubova, Katerina; Wynne, Kieran; Kolch, Walter; Rukhlenko, Oleksii S; Kholodenko, Boris N (Cell reports, 2024)
Pancreatic ductal adenocarcinoma (PDAC) presents significant challenges for targeted clinical interventions due to prevalent KRAS mutations, rendering PDAC resistant to RAF and MEK inhibitors (RAFi and MEKi). In addition, responses to targeted therapies vary between patients. Here, we explored the differential sensitivities of PDAC cell lines to RAFi and MEKi and developed an isogenic pair comprising the most sensitive and resistant PDAC cells. To simulate patient- or tumor-specific variations, we constructed cell-line-specific mechanistic models based on protein expression profiling and differential properties of KRAS mutants. These models predicted synergy between two RAFi with different conformation specificity (type I1⁄2 and type II RAFi) in inhibiting phospho-ERK (ppERK) and reducing PDAC cell viability. This synergy was experimentally validated across all four studied PDAC cell lines. Our findings underscore the need for combination approaches to inhibit the ERK pathway in PDAC.
Keywords: nádorové buněčné linie; MAP kinasový signální systém; inhibitory proteinkinas; synergismus léků; nádory slinivky břišní; MAP Kinase Signaling System; Drug Synergism; Humans; Proto-Oncogene Proteins p21(ras); Cell Line, Tumor; protoonkogenní proteiny p21(ras); Protein Kinase Inhibitors; raf Kinases; raf kinasy; Pancreatic Neoplasms; duktální karcinom slinivky břišní; lidé; Carcinoma, Pancreatic Ductal